The effect of Physiological NaCl Dilution levels and Storage Duration to Sperm Motility and Abnormality in Muscovy Duck - Fauzi, MA; WS, Rachmawati; Pramono, Edy (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
The aim of this research are to know the effects of physiological NaCl dilution levels and storage duration on sperm motility and abnormality of Muscovy duck. Materials which used in this research were semen that collected of 1 - 1,5 years of four Muscovy duck. Semen were treated by physiological NaCl dilution levels nol , three, six and nine and storage duration ( t0 = 0 minute t1 =45minutes and t2=90 minute). Replication was three tapping periode . The method of this research was laboratory experimental with Randomized Complete Blok Design (RBD) in Split Plot Design (SPD) pattern ,as main plot is Physiological NaCl dilation levels and as sub plot is storage duration. Result of the experiment showed that physiological NaCl dilution levels was very significantly influences on sperm motility (p<0,01) and significantly influences and sperm abnormality (p<0,05) . The storage duration was very significantly influences and sperm motility and abnormality (p<0,01) .Orthogonal duration polynomial assayed showed that the effect of physiological NaCl dilution levels to sperm motility had a linier regression line with the a equation as Y =69.94 - 2.65 X, r=0,49 R2=0.24 with Y presented to sperm motility and X represented to physiological NaCl dilution levels sperm and effect of storage duration to sperm motility had a linier regression line with the equation as Y =74.24-0.35 X, r =0.73 R2=0.53 with Y represented to sperm motility and X represented to storage duration . The effect of physiological NaCl dilution levels to sperm abnormality had a linier regression line with the equation as Y =5.61+0.34X, r=0.52 R2=0.27 with Y represented to sperm to abnormality and X represented to regression line with the equation as Y =6.74+0.01X, r=0.24R2=0.060 with Y represented to sperm abnormality and X represented to storage duration. It is can be concluded that a higher physiological NaCl dilation levels and storage duration caused sperm to motility decreased and sperm abnormality increased. (Animal Production 3(2): 45-52 (2001)Key Word: sperm Muscovy duck.